2003
DOI: 10.1098/rspa.2002.1095
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces and boundary conditions in continuum dislocation mechanics

Abstract: SummaryAs a guide to constitutive specification, driving forces for dislocation velocity and nucleation rates are derived for a field theory of dislocation mechanics and crystal plasticity proposed in Acharya (2001, J. Mech. Phys. Solids). A condition of closure for the theory in the form of a boundary condition for dislocation density evolution is also derived. The closure condition is generated from a uniqueness analysis in the linear setting for partial differential equations controlling the evolution of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 21 publications
1
144
0
Order By: Relevance
“…In contrast, in our work the rate of plastic distortion arises from an averaging of a fine scale theory (FDM) that incorporates the elastic theory of dislocations exactly; as for kinetics, some of the simplest realizations of the equation for dislocation density-evolution in FDM have been shown (Acharya 2003;Varadhan et al 2005) to lead to Hamilton-Jacobi equations for propagation of fronts, whose solutions can be interpreted as expansions of loops from Frank-Read sources allowing automatic annihilation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in our work the rate of plastic distortion arises from an averaging of a fine scale theory (FDM) that incorporates the elastic theory of dislocations exactly; as for kinetics, some of the simplest realizations of the equation for dislocation density-evolution in FDM have been shown (Acharya 2003;Varadhan et al 2005) to lead to Hamilton-Jacobi equations for propagation of fronts, whose solutions can be interpreted as expansions of loops from Frank-Read sources allowing automatic annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…This paper and its sequel provide a detailed account of this development and its predictions. A feature of our model that may be considered a desirable consistency property is that when the spatial averaging length scale tends to zero, our model reduces to a theory of the collective behavior of individual dislocations -applicable to finite bodies of arbitrary shape, and conveniently adapted for geometric, crystal elastic and dissipative nonlinearities as well as the effects of inertia -that can be exercised to probe mechanical behavior at the nanoscale and above, with emerging predictions representative of such (Acharya, 2001(Acharya, , 2003(Acharya, , 2004Miller and Acharya, 2004;Roy and Acharya, 2005;Varadhan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2003 research summary for this project, we reported on the development of a computational model for a dislocation mechanics based theory of plasticity building on earlier work (Acharya, 2001(Acharya, , 2003(Acharya, , 2004aRoy & Acharya, 2004). This model has been shown to make good predictions of 1. size effect 2. development of microstructure from homogeneous initial conditions under boundary conditions for homogeneous deformation in the conventional theory 3. development of a strong Bauschinger effect.…”
Section: Scope Of Workmentioning
confidence: 99%
“…Current effort is directed at a parallel implementation of the Field Dislocation Mechanics framework, posed by Acharya [22][23][24][25] . Along with parallel codes for the incompatibility and equilibrium problems, an explicit (Galerkin-Least Squares) technique has been developed for the transport of excess dislocation density.…”
Section: B Amentioning
confidence: 99%